Light beam precaution system / Mohammad Ikhwan Badiizzaman and Muhammad Naqiuddin Ramli - Badiizzaman, Mohammad Ikhwan; Ramli, Muhammad Naqiuddin (2015)
This project focuses on the programming of microcontrollers usmg a high level language. The PIC family of microcontrollers is chosen as the target microcontroller because of the low power consumption which made this microcontroller popular in portable application. Besides that, PIC also cheaper other than other microcontroller such as Arduino. This project entitles Light Beam Precaution System provides security to the house owner from any intruders or any form of robbery by automatically activating the alarm and emergency light and also display the situation by LCD connected to the microcontroller device. Through an alarm and emergency light microcontroller unit can immediately advise the house owners that the house is being robbed or an intruder has illegally trespassed their respective home. This project is mainly used laser as the light beam and photocell as sensor that will detect the light beam. The two main components will be connecting in order to activate the security system. Any obstacles that pass through the light beam will automatically cut off the circuit connection because the photocell cannot receive the light beam. So, all components which is LED, LCD and buzzer will be operated to show that there was intruders in the house.